The effect of Galilean magnification loupes on the visual acuity and working distance of dental students - Pazos, Júlia M. [UNESP]; dos Santos, Carla G. [UNESP]; Dovigo, Lívia N. [UNESP]; Garcia, Patrícia P. N. S. [UNESP] (Wiley, 2024)
Objective: This study aimed to evaluate the visual acuity and working distance of dental students using Galilean loupes at different magnification levels. Methods: The participants included 50 undergraduate dentistry students selected from each class in the second to fifth years (N = 200) of São Paulo State University, School of Dentistry, Araraquara. The response variables were (i) the working distance between the operator's eyes and the mouth of the dental phantom head, and (ii) visual acuity. The independent variables were the five levels of the Galilean magnification system (naked eye, Galilean loupe simulator without magnification, and Galilean loupes with 2.5×, 3.0×, or 3.5× magnification) and academic year. Visual acuity was measured using a miniature Snellen eye chart inserted into the Class I cavities of the maxillary molars. After verifying the assumptions of normality and sphericity, a mixed repeated measures analysis was performed (α = 0.05). Results: Statistical significance was found between the “magnification system” and “academic year” for visual acuity (p < 0.001). For the second-, fourth-, and fifth-year participants, there were no significant differences in visual acuity between the naked eye and different magnifications of the Galilean loupes, which were superior to and significantly different from that of the loupe simulator. For the working distance, statistical significance was observed in the interaction between “magnification system” and “academic year” (p = 0.008). For the third-, fourth-, and fifth-year participants, there was no significant difference in the working distance between the naked eye and different magnifications of the Galilean loupes, which were superior to and significantly different from that of the simulator. Conclusion: It was concluded that the different magnification levels of the Galilean loupes did not influence the visual acuity or distance between the eyes of the operator and the mouth of the dental phantom head in the evaluated students.
Keywords: ergonomics; Galilean loupes; occupational health; visual acuity